Murottal Surah Ar-Rahman and Aromatheraphy Lavender (Lavendula Augustfolia) Inhalation to Decrease Labor Pain on First Stage Active Phase - Azizah, Nurul; Rosyidah, Rafhani; Destiana, Evi (Universitas Islam Lamongan, 2020)
Childbirth is a natural process and causes pain, but many mothers can not resist the pain because it is influenced by stress. The study using non-phamacological pain relief therapy with aromatherapy which is believed to reduce pain and the aims to compare between murotal Al-Qur'an Surat Ar-rahman therapy and inhalation of lavender aromatherapy to reduce the intensity of labor pain when first active phase.The research design used Quasi Experimental with Non-equivalent Control Group Design method and using pretest - posttest. The population of the first phase active labor mothers in RB Nuril Masrukha Candi Sidoarjo. The technique sampling used Consecutive sampling. Data collected by observing 2 groups of labor mothers: 30 respondents listened to surah Ar-Rahman murottal and 30 respondents inhaled Lavender Aromatherapy. In both of groups, the pretest was given before treatment, then posttest was done after treatment using observation sheet assessment of pain scale with behavioral observation (FLACC behavioral scale). Data analysis using Independent Sample T-Test with a significance level α = 0.05. The results showed that the difference in pain score reduction in lavender aromatherapy inhalation was 3.26 ± 0.25, whereas in the murottal group of the Ar-Rahman Surah mean decrease in pain score was 2.62 ± 0.057 with P value <0.001, that showed a significant relationship.The conclusion is inhalation of aromatherapy lavender (Lavendula Augustfolia) and murottal surah Ar-Rahman can reduce intensity of labor pain during the first active phase, but inhalation group of aromatherapy lavender has a greater pain reduction score than murottal surah Ar-Rahman group.